How the internal family factors and external environmental factors influence the innovation capabilities and willingness of family business. - Zhang, ChenHao (2020)
A family business is a complex system composed of a family and a business. With the development of the economy, how family businesses can improve their competitiveness has become a problem that must be faced. Innovation as the source of the core competitiveness of an enterprise has a direct influence on the development of the family business. This paper aims to explore different impacts that influence the innovation performance and management of the family business. Referring to the current problems of the family business, this paper analyzes the factors which may affect the innovation of family business based on the related theories: the agency theory, resource-based view and social capital theory. Furthermore, based on the theory of family business innovation, an integrated framework is adopted to explore the different variables that influence the family business innovation capabilities and willingness and analyse the relationship between each other. At the end, suggestions to the innovation management of the family business are listed in terms of management models, governance structure and human resource management.